2016
DOI: 10.1021/acsami.6b10762
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Control of Smectic Liquid Crystals via a Combination Method of Topographic Patterning and In-Plane Electric Field Application for a Linearly Polarized Illuminator

Abstract: We dynamically controlled the configuration of layering structures built by smectic A liquid crystal molecules using the combination method of the microchannel confinement and the in-plane electric field to realize the linearly polarized illuminator and bistable structures. Once a mild in-plane electric field (∼30 V) is applied between polymeric walls, the layer configuration was changed from the toric focal conic domains to periodic zigzag patterns of alternatively packed focal conic domains. The transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…7a signify the parallelly and perpendicularly aligned molecular directors with the optic axis (l) of the full wave plate, respectively. 18,19 From the liquid crystalline texture, similar to the observations for C6 and C7, it was suggested that the C12 molecules in each layer were aligned parallel to the substrate surface, which resulted in the ion-conductive bridge between the two substrates made by the imidazolium moieties of C12.…”
Section: Introductionmentioning
confidence: 67%
“…7a signify the parallelly and perpendicularly aligned molecular directors with the optic axis (l) of the full wave plate, respectively. 18,19 From the liquid crystalline texture, similar to the observations for C6 and C7, it was suggested that the C12 molecules in each layer were aligned parallel to the substrate surface, which resulted in the ion-conductive bridge between the two substrates made by the imidazolium moieties of C12.…”
Section: Introductionmentioning
confidence: 67%
“…Since Choi et al [50] reported the exploitation of microchannels to generate periodic smectic defects, many experimental results using microchannels have been obtained [17,28,33,34,[51][52][53][54][55]. As LC materials should adopt a specifically defined orientation under limited volume and surface conditions of microchannels, the so-called confinement effect, they develop a peculiar structure in a periodic manner.…”
Section: Geometric Confinementmentioning
confidence: 99%
“…Passing through the golden age of the liquid crystal display (LCD) industry, nanotechnology based on liquid crystals (LCs) started gradually fading away from the prime line in industries once organic light-emitting diodes (OLEDs) and quantum dot technology appeared in display applications. Albeit not the most exciting material anymore, LCs are still indispensable due to their intrinsic physical properties that are easily switchable under various external stimuli, including light [1][2][3][4][5][6][7][8], temperature [9][10][11], and electric [12][13][14][15][16][17][18] and magnetic sources [19][20][21]. As the current era demands novel materials with tunable physical properties in an on/off but dynamic manner, LCs can still be one of the most appropriate media to satisfy the demand.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the intrinsic sensitivity of LCs to various external stimuli, the smectic layer curvature can be controlled via external fields as well, such as electric field and thermal field 5b,6b,29. For example, Gim and Yoon introduced an in‐plane electric field (≈30 V, 1 kHz, Figure A) to the TFCD array within microchannels, and found that columns of toric defects (Figure B) were transformed to a periodic zigzag pattern (Figure C) 28a. Further increasing the electric field to ≈100 V, the LC molecules were forced to reorient parallel to the electric field (Figure D).…”
Section: Light‐activated Liquid Crystalline Hierarchical Architecturesmentioning
confidence: 99%
“…The scale bars are 20 µm. Reproduced with permission 28a. Copyright 2016, American Chemical Society.…”
Section: Light‐activated Liquid Crystalline Hierarchical Architecturesmentioning
confidence: 99%